Intersemiotic translation of Yixiang (Image): A case study of Tang Poetry in paintings - Liang, Minna (International Journal of Communication and Society, 2023)
This paper focuses on intersemiotic translation of Yixiang, or image in western literary term, from poetry to painting by taking Tang Poetry in Paintings as a case to exemplify the translation strategies of Yixiang from verbal sign system to visual sign system. Furthermore, the meditative role of the visualized images in the target context will also be touched upon. A qualitative approach is applied in the study. Typical examples will be chosen for case analysis. It is found that the strategies of equivalence, focalization, integration, montage, addition, contrast and omission are employed by the painters. The effects of those visualized images varied in different cases. Overall, cooperating with the interlingual translations, visual languages such as color, shadow, body language of figures, picture structure are employed to help English readers better receive the poems.